Telemedicine and Virtual Reality at Time of COVID-19 Pandemic: An Overview for Future Perspectives in Neurorehabilitation - Matamala-Gomez, Marta; Bottiroli, Sara; Realdon, Olivia; Riva, Giuseppe; Galvagni, Lucia; Platz, Thomas; Sandrini, Giorgio; De Icco, Roberto; Tassorelli, Cristina (Frontiers in Neurology, 2021)
In catastrophic situations such as pandemics, patients’ healthcare including admissions to hospitals and emergency services are challenged by the risk of infection and by limitations of healthcare resources. In such a setting, the use of telemedicine interventions has become extremely important. New technologies have proved helpful in pandemics as a solution to improve the quality of life in vulnerable patients such as persons with neurological diseases. Moreover, telemedicine interventions provide at-home solutions allowing clinicians to telemonitor and assess patients remotely, thus minimizing risk of infection. After a review of different studies using telemedicine in neurological patients, we propose a telemedicine process flow for healthcare of subjects with chronic neurological disease to respond to the new challenges for delivering quality healthcare during the transformation of public and private healthcare organizations around the world forced by COVID-19 pandemic contingency. This telemedicine process flow represents a replacement for in-person treatment and thereby the provision equitable access to the care of vulnerable people. It is conceptualized as comprehensive service including (1) teleassistance with patient counselling and medical treatment, (2) telemonitoring of patients’ health conditions and any changes over time, as well as (3) telerehabilitation, i.e. interventions to assess and promote body functions, activities, and consecutively participation. The hereby proposed telemedicine process flow could be adopted on a large scale to improve the public health response during healthcare crises like the COVID-19 pandemic, but could equally promote equitable health care independent of people’s mobility or location with respect to the specialized health care center.